Introduction: Interdisciplinarity and the International Relations event horizon. (September 2020) - Daxecker, Ursula; Freyberg-Inan, Annette; Glasius, Marlies; Underhill, Geoffrey; Vigneswaran, Darshan
This Introduction contextualises this special anniversary issue of the journal. The Editors of a previous 2013 special issue of the EJIR (The End of International Relations Theory?) asked if the paradigmatic "theoretical cacophony" in IR was deep and irresolvable. We argue that there is still very much a conversation going on across 'generalist' and specialised IR journals, and that renewal and broadening is more important than boundaries per se. Meanwhile the field of International Relations has continued to broaden, absorbing much from other social science disciplines in the process. Yet IR has a problematic relationship with interdisciplinarity, often discovering as 'new' what other fields have long debated and in turn 'domesticating' these insights from other fields by fitting them into existing IR paradigms. This special issue is thus aimed above all at what 'we' in IR are not seeing from other disciplines, and we go on to argue how IR scholars might best employ 'transdisciplinary' insights to ensure the future dynamism and innovation of the field. We argue that in this context, a special effort of critical and open engagement with work that makes us uncomfortable is required and that the very notion of inter-disciplinarity takes on a new form.